Jati Diri Kaum dan Perpaduan Negara: Kajian Kes Cina Peranakan Kelantan di Malaysia: (Ethnic Identity and National Unity: A Case Study of Kelantan Peranakan Chinese in Malaysia) - Mohd Shahrul Imran Lim Abdullah, (Kajian Malaysia, 2014)
Notice of RetractionKAJIAN MALAYSIA (Journal of Malaysian Studies) herewith announces its decision to retract article "Jati Diri Kaum dan Perpaduan Negara: Kajian Kes Cina Peranakan Kelantan di Malaysia" (Ethnic Identity and National Unity: A Case Study of Kelantan Peranakan Chinese in Malaysia) by Mohd Shahrul Imran Lim Abdullah which was published in Volume 32, No.1, 2014. The decision is made upon discovery that it was not an original submission as parts of the article bear similarities to another article that was published in another journal. In addition, the author did not provide any citations to the afore-mentioned article.The journal also wishes to reiterate the importance of adherence to its author's guideline, which specifically outlines that: Manuscripts submitted for publication must be original, previously unpublished (except in the form of an abstract or as part of a published lecture or academic thesis), and not under consideration for publication elsewhere. Its publication must be approved by all Authors and tacitly or explicitly by the responsible authorities where the work was carried out, and that, if accepted, it will not be published elsewhere in the same form, in English or in any other language, without the written consent of the publisher, Penerbit Universiti Sains Malaysia.